2018
DOI: 10.1111/sji.12702
|View full text |Cite
|
Sign up to set email alerts
|

The monocyte locomotion inhibitory factor inhibits the expression of inflammation‐induced cytokines following experimental contusion in rat tibia

Abstract: Entamoeba histolityca produces the monocyte locomotion inhibitory factor (MLIF), a pentapeptide with powerful anti-inflammatory properties. MLIF may regulate trauma-induced inflammation through the effects it exerts directly or indirectly on immune cells, modulating the production and/or expression of the cytokines involved in the inflammatory processes that occur after damage. The aim of the present study was to evaluate the effect of MLIF on production of pro/anti-inflammatory cytokines after contusion in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Activity of MLIF manifests clinically as less invasive intestinal amoebiasis (produced by less virulent strains) [27] , and it is not secreted by commensal E. dispar [28] . Protective effects of MLIF have been demonstrated in rats, where it reduced cellular inflammatory infiltrate and significantly reduced inflammatory cytokines levels in contused tibia [29] . It also protects mice against cerebral malaria [30] .…”
Section: Entamoeba Histolyticamentioning
confidence: 97%
“…Activity of MLIF manifests clinically as less invasive intestinal amoebiasis (produced by less virulent strains) [27] , and it is not secreted by commensal E. dispar [28] . Protective effects of MLIF have been demonstrated in rats, where it reduced cellular inflammatory infiltrate and significantly reduced inflammatory cytokines levels in contused tibia [29] . It also protects mice against cerebral malaria [30] .…”
Section: Entamoeba Histolyticamentioning
confidence: 97%
“…It was first identified as an anti-inflammatory peptide that inhibited the migration of monocytes (Kretschmer et al, 2001;Barrientos-Salcedo et al, 2009; Silva-Garcia and Rico-Rosillo, 2011) and the expression of interleukin (IL)-1β, IL-5, IL-6, and interferon (IFN)-γ and increased the expression of IL-10 in macrophages (Utrera- Barillas et al, 2003;Rojas-Dotor et al, 2006;Silva-Garcia et al, 2008). Subsequent studies showed that MLIF participated in other biological effects, such as expression of immunomodulatory genes (Silva-Garcia et al, 2008;Rojas-Dotor et al, 2018), cell proliferation, extracellular matrix formation, angiogenesis, and axon guidance. In a previous study, we discovered that MLIF exerts a protective effect on the vascular system by acting on eukaryotic elongation factor1A1 (eEF1A1) to upregulate the expression of vascular endothelial nitric oxide synthase (eNOS) and reduce the level of ICAM-1 and VCAM-1 (Zhang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It is with great pleasure that we present the ECI2018 issue of the journal. It contains two discussion forum articles on the concept of immune tolerance, two reviews and four regular articles, which together reflect the scope and the international profile of the Journal. I hope that you will enjoy these papers and that you will continue to follow us and, above all, submit your future papers to the Scandinavian Journal of Immunology .…”
mentioning
confidence: 99%